PENGARUH METODE WAFA DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL QURAN SISWA KELAS IV DI SMPIT AL FURQON PALEMBANG - Rama Satria; Amir Rusdi; Tutut Handayani (CV. ADIBA ASIHA AMIRA, 2023)
The Wafa method is a method of learning the Qur'an by maximizing the right brain function, the hallmark of this method is reading the Qur'an with hijaz tones, SMPIT Al Furqon Palembang is one of the elementary schools that applies the Wafa method in learning the Qur'an. This Wafa method is newly applied because it previously applied the Ustmani method. The type of research used is field research using a qualitative approach with data collection techniques in the form of observation, interviews (structured and unstructured) and documentation. The data analysis technique used is the steps of data collection, data reduction, data presentation and drawing conclusions (verification). However, the teaching strategy used by the teacher is in accordance with the Wafa guidebook. The teacher uses the 5P method (Opening, Experience, Teaching, Assessment and Closing).